Macedonia at the doorstep of the European Union - Pelling, Erik (2007)
Macedonia, which applied for membership in the European Union in March 2004 and was granted candidate status in December 2005, is likely to become a member, if and when the next enlargement takes place. Now, at the doorstep of the European Union and before real accession negotiations start, it is a good idea for policy makers and the general public in Macedonia to carefully analyze the likely effects of membership and to consider what can be done to dampen the negative aspects and to get the most out of the good ones.